1981
DOI: 10.1136/jnnp.44.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis associated with epilepsy: significance of the laterality of the epileptogenic lesion.

Abstract: SUMMARY The psychiatric histories in a group of patients who had previously undergone temporal lobectomy for intractable epilepsy, were analysed for the occurrence of psychosis. The data suggest that epileptic patients with left temporal lobe lesions are especially disposed to develop a schizophrenic-like psychosis.In an earlier study of patients selected for the concordance of medically intractable epilepsy and behaviour disorder, we reported that 15 % of the patients demonstrated a schizophrenic-like psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
2
3

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 10 publications
(1 reference statement)
4
24
2
3
Order By: Relevance
“…This result is in accordance with earlier studies [5,6,15,21,22,25]. While in some of them, left-sided pathology was the most frequent finding, others found bilateral alterations [9,10,20,23].…”
Section: Discussionsupporting
confidence: 93%
“…This result is in accordance with earlier studies [5,6,15,21,22,25]. While in some of them, left-sided pathology was the most frequent finding, others found bilateral alterations [9,10,20,23].…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, although high rates of bitemporal foci were noted in some studies (45,56,67), other authors reported more lateralized foci (63,68). However in most of the studies that reported a preponderance of left temporal foci among psychotic patients, these patients were being considered for temporal lobectomy.…”
Section: Temporal Lobe Epilepsy and Psychosesmentioning
confidence: 99%
“…Prevalence in general population studies varies from 2-7,1% [8][9][10] , in general clinics from 0,8-9,2% [13][14][15][16][17][18][19][20] and in neurological or epilepsy clinics from 8,8-27% [21][22][23][24][25][26] . The purpose of this paper is to report the case of a patient with refractory epilepsy and epileptic psychosis and the value of therapeutic surgery such as temporal lobectomy in her treatment.…”
mentioning
confidence: 99%